Educating Humans - Mino, Takako; Heto, Prince Paa-Kwesi (Journal of Interdisciplinary Studies in Education, 2020)
African traditional education and soka approaches to education share a common vision of human education, which is key to transforming the education crisis facing Africa. We make this case in four steps. First, we explore the history of education in Africa to illustrate the roots of the crisis. Second, we introduce soka approaches to education, its history, and fundamental principles. Third, we analyze the convergence of African traditional education and soka approaches to education in terms of their underlying philosophies. Fourth, we investigate possible applications of both philosophies to improve schooling in Africa. The last section outlines how harnessing the insights of both philosophies will engender an African renaissance based on young people striving to live creative and contributive lives.